2019
DOI: 10.3389/fmicb.2019.00236
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Microbiota in Experimental Psoriasis Revealed by a Gnotobiotic Mouse Model

Abstract: Psoriatic patients have altered microbiota, both in the intestine and on the skin. It is not clear, however, whether this is a cause or consequence of the disease. In this study, using an experimental mouse model of psoriasis induced by imiquimod (IMQ), we show that oral treatment with a broad spectrum of antibiotics (MIX) or metronidazole (MET) alone mitigates the severity of skin inflammation through downregulation of Th17 immune response in conventional mice. Since some antibiotics, including MET, can influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 57 publications
9
53
0
Order By: Relevance
“…Another proposed mechanism underlying the link between gut dysbiosis and skin changes implies the modulation of T cells differentiation and function with an imbalance between Th17 and T regulatory (Treg) cells. In experimental model of psoriasis, it has been shown that alterations in the intestinal microbiota may promote Th17-mediated skin inflammation [12,13]. In this context, the study by Yeh et al [19] provides very interesting results, showing significantly greater changes in the gut microbiome of patients with psoriasis treated with secukinumab (interleukin-17 inhibitor) compared to ustekinumab (inhibitor of interleukin-12 and -23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proposed mechanism underlying the link between gut dysbiosis and skin changes implies the modulation of T cells differentiation and function with an imbalance between Th17 and T regulatory (Treg) cells. In experimental model of psoriasis, it has been shown that alterations in the intestinal microbiota may promote Th17-mediated skin inflammation [12,13]. In this context, the study by Yeh et al [19] provides very interesting results, showing significantly greater changes in the gut microbiome of patients with psoriasis treated with secukinumab (interleukin-17 inhibitor) compared to ustekinumab (inhibitor of interleukin-12 and -23).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical investigations provide evidence for the role of the gut microbiome in psoriasis pathogenesis. In mice with an experimental model of psoriasis induced by imiquimod, oral treatment with broad-spectrum antibiotic reduces the severity of skin inflammation through downregulation of Th17 immune response [ 12 , 13 ]. These results are supported by clinical observations based on a case series showing improvement in psoriatic skin lesions after antibiotic treatment [ 14 ], modulation of gut microbiota by probiotics [ 15 ] or fecal microbial transplantation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion of specific members of gut microbiome to intestinal epithelial cells is found to be essential for the induction of Th17 cells 20 22 . Mice exposed to antibiotics showed inhibition of psoriasis induction by a dysregulation of gut and skin microbiota 23 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased intake of ω-3 PUFA, folic acid, vitamins A, D and E may play a significant role due to their antiinflammatory properties [130][131][132]. Moreover, diet may modify gut microbiota by regulating the activity of Th17 and Treg.…”
Section: Dietary Recommendations In Patients With Psoriasismentioning
confidence: 99%
“…Moreover, diet may modify gut microbiota by regulating the activity of Th17 and Treg. The importance of the gut-skin axis in pathogenesis of psoriasis has been recently documented [131].…”
Section: Dietary Recommendations In Patients With Psoriasismentioning
confidence: 99%